Controllable design of MoS2 nanosheets anchored on nitrogen-doped graphene : toward fast sodium storage by tunable pseudocapacitance - Xu, Xin (2020)
Transition-metal disulfide with its layered structure is regarded as a kind of promising host material for sodium insertion, and intensely investigated for sodium-ion batteries. In this work, a simple solvothermal method to synthesize a series of MoS2 nanosheets@nitrogen-doped graphene composites is developed. This newly designed recipe of raw materials and solvents leads the success of tuning size, number of layers, and interplanar spacing of the as-prepared MoS2 nanosheets. Under cut-off voltage and based on an intercalation mechanism, the ultrasmall MoS2 nanosheets@nitrogen-doped graphene composite exhibits more preferable cycling and rate performance compared to few-/dozens-layered MoS2 nanosheets@nitrogen-doped graphene, as well as many other reported insertion-type anode materials. Last, detailed kinetics analysis and density functional theory calculation are also employed to explain the Na+ - storage behavior, thus proving the significance in surface-controlled pseudocapacitance contribution at the high rate. Furthermore, this work offers some meaningful preparation and investigation experiences for designing electrode materials for commercial sodium-ion batteries with favorable performance.